Glycosylation and sulphation of colonic mucus glycoproteins in patients with ulcerative colitis and in healthy subjects. - Morita, H; Kettlewell, MG; Jewell, D; Kent, P (1993)
Studies have been made of mucus glycoprotein biosynthesis in different regions of the lower gastrointestinal tract in normal patients and those with ulcerative colitis (UC), active or inactive, by means of 3H-glucosamine (3H-GlcNH2)--35S-sulphate double labelling of epithelial biopsy specimens under culture conditions. The time based rate of 3H-GlcNH2 labelling of mucus in rectal tissue was similar to that in active or inactive UC whereas the rate of 35SO4(2) labelling was significantly increased in active disease. The 3H specific activities measuring the amount of isotopic incorporation into surface and tissue mucus glycoproteins were increased in patients with active UC compared with normal or inactive subjects. The 35S specific activities did not differ significantly between patients with active UC and those in remission. In the rectum, glycosylation of mucus glycoproteins decreases with the increasing age of the patient. Regional differences in 3H-labelling of mucus components are reported for ascending colon, transverse colon, sigmoid colon, and rectum. Sulphation (35S-labelling) was higher in all parts of the colon in left sided UC. Results point to accelerated glycosylation of core proteins in the active phase of UC.